2000
DOI: 10.1038/sj.bjp.0703239
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of bradykinin B1‐receptor expression after myocardial infarction

Abstract: To determine the in¯uence of the myocardial infarction (MI) on bradykinin B1-receptor (B1R) regulation, we studied its expression in the left ventricle (LV) after MI. Rats were submitted to a permanent occlusion of the left coronary artery. Six hours, 24 h and 6 days after MI or after sham operation, left ventricular pressure (LVP) and dP/dt max were measured. LV-total RNA was extracted and B1R expression was analysed by a RNase-protection assay (each group n=6). LVP and dP/ dt max were impaired at all time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 6 publications
(9 reference statements)
4
38
1
Order By: Relevance
“…Six hours after coronary ligation, B1R expression was first detected (35). Similar to the B2R, the up-regulation of B1R expression reached its maximum 24 h after induction of MI.…”
Section: Regulation Of the B1r After Induction Of MImentioning
confidence: 74%
“…Six hours after coronary ligation, B1R expression was first detected (35). Similar to the B2R, the up-regulation of B1R expression reached its maximum 24 h after induction of MI.…”
Section: Regulation Of the B1r After Induction Of MImentioning
confidence: 74%
“…53 Furthermore, ACE itself can also upregulate the gene expression of both BK receptors by up to 11-22 fold, via a mechanism apparently unrelated to its enzymatic properties. 66 It was reported that in myocardial tissues of rats submitted to acute myocardial infarct there was a significant upregulation of both B 1 R and B 2 R detectable within 6 h and reaching its peak at 24 h, 57,67,68 with the B 1 R expression returning gradually to baseline in the next 3-6 days, whereas the B 2 R overexpression appears to last much longer. Thus, myocardial ischemia-whether due to Ang II-induced coronary constriction or to mechanical coronary obstruction-is associated with an upregulation of both BK receptors that would seem to be compensatory, but may also have noxious effects as well.…”
Section: B 2 R-mediated Cardioprotection Post Ischemic Injurymentioning
confidence: 99%
“…These data indicated that potentiation of BK in the absence of B 1 R is insufficient to provide full cardioprotection, despite upregulated B 2 R; however, in the setting of absent B 2 R and upregulated B 1 R, the potentiation of BK actually seems to inflict further cardiac tissue damage. 68 In view of the known proinflammatory and noxious B 1 R-mediated actions and the loss of the metabolic B 2 R-mediated properties that would enhance glucose utilization by the ischemic myocardium, it is not surprising that BK potentiation in the setting of absent B 2 R and upregulated B 1 R would exert an additional detrimental effect on the injured myocardium.…”
Section: B 2 R-mediated Cardioprotection Post Ischemic Injurymentioning
confidence: 99%
“…For example, administration of an ACEI shortly after acute myocardial infarction reduced the incidence of death or development of severe congestive heart failure (3,4). Acute myocardial infarction also induces B 1 receptor expression (39). The induction and activation of the B 1 receptor could prove advantageous under various stressful conditions, ranging from infection to cardiovascular disorders (15).…”
Section: Ace Inhibitors Activation Of Bk B 1 Receptormentioning
confidence: 99%